Snake biodiversity: Educational tools for species conservation (Research, Society and Development, 2022)
Snakes are classified into two groups: as venomous, because they have an inoculating apparatus to inoculate the venom and non-venomous, they have venom but do not have an inoculating apparatus. It is important to know about snakes because they are considered dangerous animals, and because they are essential to the ecological chain and the extinction of these animals can have a great impact on nature. Thus, this study aimed to discuss the biodiversity and conservation of snakes through environmental education with students from a public school in the city of São Luís. Questionnaires on their perception of the subject were applied, followed by lectures and, finally, visits to the herpetological exhibition with organisms from the Zoology collection of UEMA. About the knowledge of the theme, more than 70% of the students knew about biodiversity, and 25% answered that they did not know about biodiversity. 30% of the students answered that destruction of snake habitat brings consequences to the environment. About the disappearance of snakes, only 32% answered correctly environmental imbalance, showing that there is a fear to preserve snakes. They were asked about what to do to preserve snakes and 60% answered about the conservation of natural areas. The lectures and exhibitions served as a learning tool, a moment of discussion, and a problematization about the importance of snakes for the ecosystem. Thus, environmental education activities are important to promote knowledge and understanding of the importance of this group. Thus, these activities help to conserve biodiversity.